2021
DOI: 10.1021/acs.langmuir.1c00236
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Efficient Nanofilm Pure Evaporation on Nanopillar Surfaces

Abstract: Molecular dynamics simulations were conducted to systematically investigate how to maintain and enhance nanofilm pure evaporation on nanopillar surfaces. First, the dynamics of the evaporation meniscus and the onset and evolution of nanobubbles on nanopillar surfaces were characterized. The meniscus can be pinned at the top surface of the nanopillars during evaporation for perfectly wetting fluid. The curvature of the meniscus close to nanopillars varies dramatically. Nanobubbles do not originate from the soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Unlike traditional computational fluid dynamics simulations, the MD method can directly explore the nanoscopic origins, elucidate phenomena from a molecular perspective, and provide a fundamental understanding that is not accessible by experiments; thus, it has been widely used to investigate various interfacial phenomena, such as droplet wetting, , impact, coalescence, , and evaporation, , as well as liquid boiling and vapor condensation. , In this paper, nonequilibrium molecular dynamics simulations were performed to investigate the nanoscale thin-film boiling process. Aiming at understanding the initial bubble behaviors and the heat and mass transfer performance, this work was conducted and illustrated around the following objectives: (1) capturing the triple-phase interface to record the lifetime of nanobubbles, (2) visualizing the internal fluid flow and thermal characteristics, (3) studying the effects of surface physicochemical properties on boiling performance, and (4) revealing the essential regulation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional computational fluid dynamics simulations, the MD method can directly explore the nanoscopic origins, elucidate phenomena from a molecular perspective, and provide a fundamental understanding that is not accessible by experiments; thus, it has been widely used to investigate various interfacial phenomena, such as droplet wetting, , impact, coalescence, , and evaporation, , as well as liquid boiling and vapor condensation. , In this paper, nonequilibrium molecular dynamics simulations were performed to investigate the nanoscale thin-film boiling process. Aiming at understanding the initial bubble behaviors and the heat and mass transfer performance, this work was conducted and illustrated around the following objectives: (1) capturing the triple-phase interface to record the lifetime of nanobubbles, (2) visualizing the internal fluid flow and thermal characteristics, (3) studying the effects of surface physicochemical properties on boiling performance, and (4) revealing the essential regulation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The miniaturization and integration of micro/nanoelectronic devices give rise to the high heat flux density of these devices and irresistible outcome of overheating. The failure rate of the device caused by overheating increases exponentially when its temperature is over 75 °C, which appeals to the development of efficient thermal management techniques to solve these thermal issues. , Due to the full utilization of both sensible heat and latent heat of coolants, the phase-change cooling technology possesses a larger capacity of heat removal and has attracted extreme attention currently. As a high-efficiency method of phase-change cooling, flow condensation in microchannels, which serves to cool the boiling vapor heated by the heat sink, is crucial to reduce the energy and coolant input and thus improve the whole efficiency of the cooling system. Lots of studies have investigated flow condensation characteristics in microchannels, which reveal that heat transfer coefficients of condensation in microchannels could be enhanced with an increase in mass flux and a decrease in diameter. On the other hand, previous investigations have found that condensation flow patterns in microchannels are mainly annular flow, slug flow, and bubbly flow, rather than the traditional stratified flow, which is due to the dominance of shear and surface tension at interfaces in microchannels. Due to the flourishing development of manufacturing technology, the size of electronic devices is minimized from the microscale to the nanoscale, at which the system spatial scale is comparable to the molecular mean free path .…”
Section: Introductionmentioning
confidence: 99%